Occupational Health Inequalities by Issues on Gender and Social Class in Labor Market: Absenteeism and Presenteeism Across 26 OECD Countries - Kwon, Min Jung (Frontiers in Public Health, 2020)
Background: This study aimed to examine the health disparities among working populations of 26 OECD countries through absenteeism and presenteeism, and to explain the combined effects of gender, work-life imbalance, occupational class, and labor market gender inequality factors on the occurrence of them. Methods: We investigated nested data on 30,131 wage workers across 26 OECD countries. At the country level, macro indicators representing labor market gender inequality were collected from OECD database. Multi-level logistic analysis was used to analyze the main and interacting effects of explanatory variables on absenteeism and presenteeism. Results: This study revealed a negative relationship between gender inequalities in the labor market and the incidence of absenteeism and presenteeism. After controlling for relevant individual- and country-level factors, the gender wage gap was associated with a decrease in absenteeism and presenteeism but the gender gap in the employment rate had a similar effect only on presenteeism. In addition, these country-level factors worked differently for the risk of absenteeism and presenteeism among groups of workers by gender, level of work-life imbalance, employment condition, and occupational class. Conclusion: Workers in societies with separate gender roles and structural inequalities in the labor market reported lower levels of absenteeism and presenteeism, which was explained by an association between the double burden of work and family life and occupational health. In other respects, however, gender egalitarian policies may play an essential role in preventing health disadvantages for unfavorable working groups of women, non-permanent contract and manual job.